The Holo-Transcriptome of a Calcified Early Branching Metazoan - Germer, Juliane; Cerveau, Nicolas; Jackson, Daniel J. (Frontiers in Marine Science, 2017)
Symbiotic interactions are widespread throughout the animal kingdom and are increasingly recognized as an important trait that can shape the evolution of a species. Sponges are widely understood to be the earliest branching clade of metazoans and often contain dense, diverse yet specific microbial communities which can constitute up to 50% of their biomass. These bacterial communities fulfil diverse functions influencing the sponge’s physiology and ecology, and may have greatly contributed to the evolutionary success of the Porifera. Here we have analyzed and characterized the holo-transcriptome of the hypercalcifying demosponge Vaceletia sp. and compare it to other sponge transcriptomic and genomic data. Vaceletia sp. harbours a diverse and abundant microbial community; by identifying the underlying molecular mechanism of a variety of lipid pathway components we show that the sponge seems to rely on the supply of short chain fatty acids by its bacterial community. Comparisons to other sponges reveal that this dependency may be more pronounced in sponges with an abundant microbial community. Furthermore, the presence of bacterial polyketide synthase genes suggests bacteria are the producers of Vaceletia’s abundant mid-chain branched fatty acids, whereas demospongic acids may be produced by the sponge host via elongation and desaturation of short-chain precursors. We show that the sponge and its microbial community have the molecular tools to interact through different mechanisms including the sponge’s immune system, and the presence of eukaryotic-like proteins in bacteria. These results expand our knowledge of the complex gene repertoire of sponges and show the importance of metabolic interactions between sponges and their endobiotic microbial communities.